2011
DOI: 10.1002/jcb.23279
|View full text |Cite
|
Sign up to set email alerts
|

Saitohin, which is nested within the tau gene, interacts with tau and Abl and its human‐specific allele influences Abl phosphorylation

Abstract: Saitohin (STH) is a gene unique to humans and their closest relatives whose function is not yet known. STH contains a single polymorphism (Q7R); the Q allele is human-specific and confers susceptibility to several neurodegenerative diseases. In previous work, we discovered that STH interacts with Peroxiredoxin 6 (Prdx6), a unique member of that family which is bifunctional and whose levels increase in Pick’s disease. In this study, we report that STH also interacts with tau and the non-receptor tyrosine kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The single exon coding ORF within MAPT 5’intron 11 has been characterized by transcript expression and proteomic detection in certain hominoids [ 45 , 46 ]. We reinvestigated its molecular evolution based on automated annotation of extended protein variants in other primates and abundant new RNA Seq data for transcript expression as part of the genome annotation pipeline of various species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The single exon coding ORF within MAPT 5’intron 11 has been characterized by transcript expression and proteomic detection in certain hominoids [ 45 , 46 ]. We reinvestigated its molecular evolution based on automated annotation of extended protein variants in other primates and abundant new RNA Seq data for transcript expression as part of the genome annotation pipeline of various species.…”
Section: Resultsmentioning
confidence: 99%
“…3d ) merits further comparative functional studies [ 40 ]; the saitohin ORF variation between monkeys and certain Catarrhine apes (Fig. 6 ) may be relevant to the more accentuated development of dementias in the latter group [ 45 , 46 ]; the identification of key regulatory elements for transcription and alternative splicing in promoter and intronic regions and the impact of epigenetic changes [ 13 ] can also be studied by genomic bioinformatics analogous to the novel protein analyses presented here.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly expressed in the placenta, muscle, fetal brain and adult brain. In numerous association studies [30][31][32], it has been shown to interact with tau, but also with peroxiredoxin 6 [33], which has antioxidant and phospholipase activity, and with the Abelson kinase [34]. Interestingly, Abelson is widely expressed but is notably highly expressed in hyaline cartilage [35], which could give us a link to the dysmorphic features involving notably the nose in affected patients.…”
Section: Discussionmentioning
confidence: 94%
“…Alternative splicing of hinge-region exon 6 gives rise to Tau variants that lack the domain responsible of microtubule binding, and is mentioned that alters Tau function (Andreadis, 2011;Luo et al, 2004). Saitohin (STH), an intronless gene encoding an open reading frame of 128 amino acids, is located in the intron between exons 9 and 10 of the human Tau gene (Wang et al, 2011). Recently has been associated the existence of a polymorphic form with AD, but is still under research.…”
Section: Tau Proteinmentioning
confidence: 99%
“…In this regions is present various PPXXP or PXXP motifs which allow Tau protein to interacts with SH3 domains of diverse proteins such as Src family members like Fyn, Lck, Src (Lee, 2005;Lee et al, 1998;Scales et al, 2011) and others like PCL- (Hwang et al, 1996;Jenkins &Johnson, 1998). Is also mentioned that STH interacts with Tau and Abl and influences in Abl phosphorylation (Wang et al, 2011), but this phenomena needs further research.…”
Section: Tau and Amyloid-β Conformational Change To β-Sheet Structurementioning
confidence: 99%